2022
DOI: 10.3390/antibiotics11091172
|View full text |Cite
|
Sign up to set email alerts
|

Plethora of Antibiotics Usage and Evaluation of Carbapenem Prescribing Pattern in Intensive Care Units: A Single-Center Experience of Malaysian Academic Hospital

Abstract: Excessive antibiotic consumption is still common among critically ill patients admitted to intensive care units (ICU), especially during the coronavirus disease 2019 (COVID-19) period. Moreover, information regarding antimicrobial consumption among ICUs in South-East Asia remains scarce and limited. This study aims to determine antibiotics utilization in ICUs by measuring antibiotics consumption over the past six years (2016–2021) and specifically evaluating carbapenems prescribed in a COVID-19 ICU and a gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…The carbapenem family of antibacterials is well known for its broad range of effectiveness, making them the most frequently prescribed antibiotics in intensive care units for drug-resistant infections [15,16]. A recent study found that prior exposure to MER was present in 27.60% of patients with CDI, preceded only by piperacillin/tazobactam (PIP/TAZ) in 77.60% of cases of CDI [17].…”
Section: Introductionmentioning
confidence: 99%
“…The carbapenem family of antibacterials is well known for its broad range of effectiveness, making them the most frequently prescribed antibiotics in intensive care units for drug-resistant infections [15,16]. A recent study found that prior exposure to MER was present in 27.60% of patients with CDI, preceded only by piperacillin/tazobactam (PIP/TAZ) in 77.60% of cases of CDI [17].…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenem consumption should be kept to a minimum to conserve carbapenem efficacy in the future [ 8 , 9 , 10 , 11 ]. In Japan, carbapenem consumption accounted for approximately 10% of all parenteral antimicrobial consumption [ 12 ].…”
Section: Introductionmentioning
confidence: 99%